Effect of the morphology of silver layer on electrical conductivity and electrochemical performance of silver/reduced graphene oxide/cotton fabric composite as a flexible supercapacitor electrode. (October 2021) - Karami, Zahra; Youssefi, Mostafa; Raeissi, Keyvan; Zhiani, Mohammad
Highlights: Ag/RGO/CF composite electrodes were prepared using three different ESP methods. ESP procedure strongly affected the shape, particle size, and density of AgNPs on the electrode surface. The compromise between the mass loading of AgNPs, conductivity, and electrochemical performance is required to prepare the electrode with high energy storage ability. an optimized amount of AgNPs was required to achieve an electrode with the interconnected network of AgNPs as well as the porous morphology, yielding an excellent energy storage performance Abstract: Three different electroless silver plating (ESP) methods were used to prepare the silver nanoparticles (AgNPs)/reduced graphene oxide (RGO)/cotton fabric (CF) composite electrodes. The Ag/RGO/CF composites were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), sheet resistance, water contact angle, and thermal gravimetric analysis (TGA). The electrochemical performance was investigated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and galvanostatic charge-discharge (GCD). The effect of the ESP method on morphological, structural, electrical, and electrochemical properties of the composite electrodes was evaluated. It was found that the compromise between the amount of deposited AgNPs, conductivity, and electrochemical performance is required to prepare the electrode with high energy storage ability. The simple and rapid ESP method, which was performed on the surface of RGO/CF at room temperature, achieved the electrode with the interconnected porous morphology providing the highest energy storage performance. This morphology provided easy electron transfer, short ion diffusion pathways, and increased penetration of the ions into the electrode materials, leading to improved electrochemical performance. The produced electrode showed a noticeable specific capacitance of 350±9 Fg −1 at a scan rate of 5 mV s −1 in 0.5 M H2 SO4 electrolyte and retained 87 % of initial capacitance after 1000 mechanical bending cycles. The symmetric supercapacitor cell based on this electrode exhibited high specific energy of 43.2 Wh Kg −1 and excellent cycle life (95.8 % retention after 3000 charge-discharge cycles). The supercapacitor with asymmetric configuration exhibited enhanced specific energy of 70.6 Wh Kg −1 due to the extended operating voltage range.